Anti-Social Gaming "Sakebi" - France, Calum (2017)
Virtual Reality is gradually becoming more integrated into the public domain. There is a wealth of research that supports this notion and has investigated how users interact with Virtual Reality devices and how observers react to users. The purpose of this study was explorative to investigate a gap in the literature surrounding prominent vocal interactions with a virtual reality device in the public space. The aim was to investigate whether participants would perform unconventional behaviour within the public space by shouting out phrases, and what effect this would have on spectators, levels of introversion and extraversion were also tested to determine differences. The study began with participants taking part in a public Virtual Reality Game "Sakebi" the game consisted of three environments. Each developed to provide different themes (Horror, Neutrality, Pleasant). The participants consisted of groups of four. Each participant transitioned through four roles and each tool it in turns to complete all experiences and act as spectators.They were observed throughout the experience via video recording. They then all participated in a group interview to communicate their experiences. The findings suggest participants with little reservation will shout in a public environment, due to the immersion of the device. However the horror themed environment was reported as the most natural to shout in, spectators enjoyed the experience and at times found it more enjoyable than the role as a user. Introversion and Extraversion did not appear to be related to an individual's willingness to shout in a public place. Further findings are critically discussed